THE The Effect Of Brand Image On The Decision Process To Visit Tourist In Cicalengka Dreamland - Pramudya, Aria Dimas; Safa’atul Barkah, Cecep (RELASI : JURNAL EKONOMI, 2024)
Increased business potential in the tourism industry, especially in the provinces of West Java and Bandung Regency, so that many companies are competing to be the best in this increase. PT. Tahfidz Land Group with its product Cicalengka Dreamland is a tourist spot that introduces natural and Islamic nuances. This is done as a business strategy in increasing the tourism industry. This study aims to determine the effect of brand image on the decision process to visit tourists. This study uses a quantitative method with a descriptive verification approach. The sampling technique was carried out using probability sampling with simple random sampling. This study uses simple linear regression analysis, coefficient of determination and hypothesis testing to determine the effect. The population in this study are tourists who have visited Cicalengka Dreamland in 2022, totaling 100 respondents. The results of the study reveal that brand image has a positive influence on the visiting decision process. Thus, the better the brand image, the tourists will follow the visiting decision process pattern. Suggestions that can be given are increasing marketing through social media, providing reservations through online travel agents, and improving facilities such as providing shaded equipment rental because Cicalengka Dreamland is in a proving area.